Rapid recovery of desert shrubs is attributed to imbalance of water supply to demand after disturbance in Northwest China - Hai Zhou; Xiangyan Feng; Zhibin He; Qiyue Yang; Heng Ren; Wenzhi Zhao (Ecological Processes, 2024)
Abstract Background Disturbance is a key driver of changes in terrestrial ecosystems, especially in water limited regions. In the desert ecosystem of Northwest China, shrubs are often foraged by camels and this causes the shrubs lost their aboveground tissues. Although the aboveground tissue could recover after the disturbance, the mechanisms of resprouts’ recovery after the disturbance are still poorly understood. We investigated the morphological and physiological characteristics and root water uptake sources of resprouts and non-disturbed seedlings of four desert shrub species that were often foraged by camels. Results The results showed that the resprouts grew rapidly after the removal of aboveground tissue. The height and aboveground biomass of resprouts reached the level of 5-year-old seedlings following a growing season. Compared to un-disturbed seedlings, higher leaf water potential, leaf hydraulic conductance and photosynthesis rate were observed in resprouts, indicating that resprouts grew rapidly after disturbance. Furthermore, we found that the root water uptake source did not change after disturbance. This indicated that the roots of resprouts kept intact water uptake capacity after disturbance, which could keep supplying sufficient water to the aboveground tissue. Due to the removal of aboveground tissue of the resprouts, the water demand of aboveground tissue decreased, which induced an imbalance of water supply from roots to demand of aboveground tissues of resprouts. This explained the improved physiological performance and rapid recovery of resprouts after disturbance. Conclusions The imbalance of water supply to demand contributes to the rapid recovery of desert shrubs after disturbance. The findings provide insight into the eco-physiological mechanism for the maintenance of desert ecosystems that are facing disturbance.